Criminal Liability for the Act of Playing Judge Alone (Eigenrichting) Against the Perpetrators of the Crime of Theft in the Criminal Code at the Sukahaji Police Station - Nur Hakim, Justitio; Harmono, Harmono; Nurhaqi, Ari (Ann Publisher, 2025)
Background. Vigilante cases generally exist in the crime of theft; the perpetrator is caught off because of the crime committed by the perpetrator, and residents who know about the incident will use their collective power to chase, hit, and gang up on the perpetrator. The act of vigilante itself is how to determine the criminal responsibility of the perpetrator, as well as the settlement of the crime of theft. Aim. This study aims to determine the responsibility of vigilante crime perpetrators and their settlement with the Majalengka Police. Methods. The method used is normative juridical, sourced from data taken at the Sukahaji Police Station.Result. The meaning of criminal liability or guilt must be expanded while still considering the balance between the interests of individuals and the interests of the wider community. Furthermore, he reminded us that consideration must be made very carefully, especially when making a drastic leap from the conception of error that is expanded in such a way to the conception of no error at all. The latter is the deepest root of the values of justice based on Pancasila. Conclusions. The concept of vigilante justice (eigenrichting) is not explicitly addressed in Indonesian criminal law within the Criminal Code. Individuals engaging in vigilante actions (eigenrichting) may face penalties commensurate with their conduct and can be prosecuted under Article 351 of the Criminal Code regarding persecution, Article 170 concerning violence, Article 406 paragraph (1) pertaining to destruction, Article 338 regarding intentional homicide, and Article 354 concerning severe persecution.Implementation. The reform of the Criminal Law in Indonesia, specifically the Criminal Code Bill, has not explicitly addressed the act of vigilantism (eigenrichting). Typically, vigilantism is resolved through restorative justice, which seeks to reconcile the parties involved without resorting to legal proceedings.